TECHNOLOGY + CONTENT = TEACHING OPPORTUNITIES - de Cascia da Costa, Francisca; Cristina Medeiros de Azevedo Silva, Ana; Amilton da Costa, José; Medeiros, Salésia (Revista Gênero e Interdisciplinaridade, 2025)
The text highlights the importance of digital technologies, especially the internet, in transforming education, emphasizing their role in communication, access to information, and the collaborative construction of knowledge. The internet breaks down barriers of time and space, facilitating the exchange of experiences and promoting student autonomy in the learning process. Furthermore, it emphasizes that the integration of these tools into education requires reflection and planning on the part of teachers and institutions, ensuring their use is effective and meaningful, contributing to methodological innovation and the development of more critical and participatory students.